LABELLING OF CHILDREN AS WITCHES IN EKET, AKWA IBOM STATE, NIGERIA (2014)
Witchcraft labelling, which is mostly associated with the aged, and which attracts ostracism and stigmatisation, is a common phenomenon in traditional African societies to address the question of social order. Existing studies have focused on adult witches and approached the discourse from the perspectives of power relations, social control, gender bias and occult economy, paying inadequate attention to the labelling of children as witches and its implications for social order in Eket, Akwa-Ibom state. This study, therefore, examined the conception of witchcraft held by Eket people, the raison d‟être for child labelling, its consequences on social order and the reactions of the community and organisations in Eket. The study adopted Taussig's Commodity Fetishism. Ethnography was conducted at two levels: the Eket community and the Child Rights and Rehabilitation Network (CRARN), a centre for labelled children. Participant observation was undertaken at the CRARN centre and selected churches. In-depth interviews were conducted with 95 informants purposively selected from Eket: one paramount ruler, two village heads, two women leaders, 25 men; 25 women; five police officers, five parents of labelled children; five clergy, five members each from the three churches studied; 10 labelled children from among street children. At CRARN, in-depth interviews were conducted with 80 purposively sampled children and four key informants. Data were analysed qualitatively. In Eket, witchcraft was widely constructed in the form of behavioural deviation with familiars signifying witches. Labelled were individuals, considered to be maliciously evil, covertly jealous and resentful of others' good fortune. Children manifesting these traits were labelled as witches and abandoned to the street. Labelling was linked to profiteering on religious pretext resulting from exorcist activities for which huge sums of money were charged by the clergy in "prayer houses" as attested to by the parents of labelled children. It also latched onto familial instability, economic crisis and serial misfortunes. Labelled children blamed their predicaments on step mother's imbroglio which offered the readiest pretext to get rid of them. Sampled social workers affirmed that many poor parents used labelling to side track parental responsibilities to disavow their children and dispense with them. Street living, resulting from witchcraft labelling, constituted an aberration of order because it exposed them to child trafficking, separation from their families and deviant sub-cultures. The traditional rulers expressed the view that indiscriminate labelling of children defeated the original purpose of using witchcraft labelling for strengthening social order. While the community ostracised and tortured the children, CRARN responded positively by rescuing and rehabilitating them. Eket child witch labelling, motivated by social, economic and religious reasons, and received differently by the community and CRARN, had exclusively negative effects on labelled children and bore dangerous implications for the Eket community. The extremity and mercenary dimensions of the practice defeated its traditional goal of preserving social order in Eket society. Therefore, efforts such as those by CRARN should be intensified to rehabilitate the children and reconcile severed child-parent relationships.